A kind of low absorption and high emission anti-corrosion thermal control coating on aluminum alloy surface and preparation method thereof

The preparation of low absorption and high emission anti-corrosion thermal control coatings on the surface of aluminum alloys through pulsed microarc oxidation and sol-gel composite technology has solved the problem of insufficient thermal control and anti-corrosion performance in spacecraft applications, and achieved wider aerospace applications and weight reduction benefits.

CN116005223BActive Publication Date: 2025-05-02BEIJING XCHD SCI & TECH DEV CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211666195.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-23
Publication Date
2025-05-02
Estimated Expiration
2042-12-23

AI Technical Summary

Technical Problem

High-strength aluminum alloys face insufficient thermal control and corrosion resistance in spacecraft applications, especially in marine climates, which are difficult to meet the needs of high-reliability service.

Method used

Using pulsed microarc oxidation technology and sol-gel composite technology, low-absorbing and high-emission anti-corrosion thermal control coatings are prepared on the surface of aluminum alloy. The method includes electrolyzing in an electrolyte cell with phosphate, silicate and zirconate electrolyte to form an initial thermally controlled coating and further enhancing the performance of the coating by spraying a surface modifier of a silicon sol and a metal thermally controlled salt.

Benefits of technology

It has achieved low absorption and high emission characteristics on the surface of aluminum alloy and good corrosion resistance, expanded the application range of high-strength aluminum alloys in the aerospace field, and enabled the material to give full play to its weight-reducing advantages.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a low-absorption and high-emission anti-corrosion thermal control coating on the surface of an aluminum alloy and a preparation method thereof, and relates to the field of surface engineering technology. The method comprises: S1, placing the aluminum alloy after pretreatment as an anode in an electrolytic cell, using a pulse micro-arc oxidation power supply to electrolyze the electrolyte in the electrolytic cell to obtain an initial thermal control coating formed on the surface of the aluminum alloy, the electrolyte comprising phosphate, silicate and zirconate, the concentration of phosphate is 1-20 g / L, the concentration of silicate is 1-20 g / L, and the concentration of zirconate is 0.1-5 g / L; S2, coating the surface modifier on the surface of the aluminum alloy treated in step S1, and forming a low-absorption and high-emission anti-corrosion thermal control coating on the surface of the aluminum alloy after the surface modifier is solidified, the surface modifier comprising silica sol and metal thermal control salt, the particle size range of silica sol is 10-80 nm, the concentration of silica sol is 5-20 wt%, and the concentration of metal thermal control salt is 0.1-5 wt%. The thermal control coating of the present invention has the characteristics of low absorption, high emission and corrosion resistance, and expands the application of aluminum alloy in the aerospace field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of surface engineering technology, and in particular to a low-absorption and high-emission anti-corrosion thermal control coating on an aluminum alloy surface and a preparation method thereof. Background Art

[0002] The development of lightweight spacecraft has put forward an urgent demand for weight reduction of structures and mechanisms. High-strength aluminum alloys represented by Al-Cu-Mg and Al-Zn-Mg-Cu generally have a tensile strength greater than 480MPa. The alloys have good specific strength and specific stiffness, and excellent high and low temperature mechanical properties. They have broad application prospects in the lightweight manufacturing of spacecraft. However, due to the high solute atom content and poor corrosion resistance of this type of alloy, it is difficult to meet the high-reliability service requirements of spacecraft in marine climate environments when directly used.

[0003] During the spacecraft's in-orbit flight, the maximum temperature can reach over 200°C when exposed to solar radiation. Combined with the heat released when the payload is working, the excessively high temperature will have a serious impact on the stable operation of the spacecraft's instruments and equipment. Applying thermal control coatings on the surface of relevant equipment to reduce the absorption of solar radiation heat by the equipment and to effectively radiate the internal heat outward in time is important for the stable operation of spacecraft in orbit. However, the emissivity of high-strength aluminum alloys is generally low, and they cannot effectively radiate heat outward.

[0004] Therefore, in order to solve the thermal control and corrosion protection problems faced by high-strength aluminum alloys in aerospace applications, it is urgent to develop low-absorption and high-emission anti-corrosion thermal control coating technology on the surface of high-strength aluminum alloys. Summary of the invention

[0005] The technical problem to be solved by the present invention is how to provide a thermal control coating having low absorption and high emission characteristics and good corrosion resistance on the surface of a high-strength aluminum alloy and a preparation method thereof.

[0006] In order to solve the above problems, in a first aspect, the present invention provides a method for preparing a low-absorption and high-emission anti-corrosion thermal control coating on an aluminum alloy surface, comprising:

[0007] S1, placing the pre-treated aluminum alloy as an anode in an electrolytic cell, using a pulsed micro-arc oxidation power supply to electrolyze the electrolyte in the electrolytic cell to obtain an initial thermal control coating formed on the surface of the pre-treated aluminum alloy, wherein the electrolyte comprises phosphate, silicate and zirconate, the concentration of phosphate is 1 to 20 g / L, the concentration of silicate is 1 to 20 g / L, and the concentration of zirconate is 0.1 to 5 g / L;

[0008] S2, coating the surface modifier on the surface of the aluminum alloy treated in step S1, and forming a low-absorption and high-emission anti-corrosion thermal control coating on the surface of the aluminum alloy after the surface modifier is solidified, wherein the surface modifier includes silica sol and metal thermal control salt, the particle size range of the silica sol is 10 to 80 nm, the concentration of the silica sol is 5 to 20 wt%, and the concentration of the metal thermal control salt is 0.1 to 5 wt%.

[0009] A further technical solution is that in step S1, the electrolyte in the electrolytic cell is electrolyzed at a current density of 1A·dm -2 ~30A·dm -2 , forward voltage 300V~650V, power frequency 50Hz~2000Hz, duty cycle 10%~60%

[0010] A further technical solution is that in step S1, the temperature of the electrolyte is 10-40° C. and the pH value is 8.5-14.0.

[0011] A further technical solution is that in step S1, the time for electrolyzing the electrolyte in the electrolytic cell is 5 to 60 minutes.

[0012] Its further technical solution is that step S2 comprises:

[0013] The surface modifier is coated on the surface of the aluminum alloy treated in step S1 by spraying, and the surface modifier is cured by keeping at 60-100° C. for 2-8 hours to obtain a low-absorption and high-emission anti-corrosion thermal control coating on the surface of the aluminum alloy, wherein the number of spraying is 3-8 times.

[0014] A further technical solution is that in step S1, the phosphate includes Na3PO4, Na5P3O 10 At least one of .

[0015] A further technical solution is that in step S1, the silicate includes at least one of Na2SiO3 and K2SiO3.

[0016] A further technical solution is that in step S1, the zirconate includes at least one of K2ZrF6 and Zr(NO3)4.

[0017] A further technical solution is that in step S2, the metal thermal control salt includes at least one of zinc sulfate, silver nitrate and magnesium phosphate.

[0018] A further technical solution is that, before step S1, the method further includes:

[0019] The aluminum alloy is sandblasted with 150-250 mesh white corundum, and the surface of the aluminum alloy after sandblasting is cleaned with acetone and alcohol in sequence, and dried with compressed gas to obtain the aluminum alloy after pre-treatment.

[0020] A further technical solution is that the aluminum alloy is an Al-Zn alloy or an Al-Cu alloy.

[0021] In a second aspect, an embodiment of the present invention provides a low-absorption and high-emission anti-corrosion thermal control coating on the surface of an aluminum alloy, which is prepared by the method described in the first aspect.

[0022] Compared with the prior art, the technical effects achieved by the present invention include:

[0023] (1) The present invention utilizes micro-arc oxidation and sol-gel composite technology to prepare a low-absorption and high-emission anti-corrosion thermal control coating on the surface of high-strength aluminum alloy, which solves the problem of poor compatibility between thermal radiation performance and anti-corrosion performance of traditional thermal control coatings on the surface of high-strength aluminum alloy and the resulting limited application range of alloy materials, expands the application of high-strength aluminum alloy in the aerospace field, and enables this type of material to more fully exert its weight reduction advantages.

[0024] (2) The low-absorption and high-emission anti-corrosion thermal control coating on the surface of high-strength aluminum alloy prepared by the present invention has a coating thickness of 40 to 150 μm, a bonding strength of level 1, a coating solar absorptivity of 0.18 to 0.25, an infrared emissivity of 0.85 to 0.97, salt spray resistance ≥ 800 h, and moisture and heat resistance ≥ 1000 h. After 100 thermal cycles at -196°C to +100°C, no damage or shedding occurs. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments are described clearly and completely below. Obviously, the embodiments described below are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.

[0027] It should also be understood that the terms used in this specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. As used in the specification of the present invention and the appended claims, unless the context clearly indicates otherwise, the singular forms "a", "an" and "the" are intended to include plural forms.

[0028] Embodiment 1:

[0029] This embodiment provides a method for preparing a low-absorption and high-emission anti-corrosion thermal control coating on an aluminum alloy surface, which is specifically prepared according to the following steps:

[0030] (1) using 200 mesh white corundum to sandblast an aluminum alloy (7A04), then using acetone and alcohol to clean the surface of the aluminum alloy after sandblasting, and using compressed air to dry it to obtain a pre-treated aluminum alloy;

[0031] (2) placing the aluminum alloy treated in step (1) in an electrolytic cell, with the aluminum alloy as the anode and the stainless steel electrolytic cell as the cathode, and using a pulsed micro-arc oxidation power supply to supply power at a current density of 6 A·dm -2 , forward voltage 550V, power frequency 500Hz, duty cycle 50%, electrolyte temperature 40℃, pH value 9, reaction for 30min, to obtain a low absorption, medium and high emissivity thermal control coating (initial thermal control coating) grown in situ on the surface of aluminum alloy. The electrolyte used includes Na2SiO3, Na3PO4 and K2ZrF6, the concentration of Na2SiO3 is 10g / L; the concentration of Na3PO4 is 10g / L, and the concentration of K2ZrF6 is 1g / L.

[0032] (3) An anti-corrosion / thermal control enhanced surface modifier was prepared using silica sol and metal thermal control salt as raw materials. The surface modifier was sprayed on the surface of the aluminum alloy after micro-arc oxidation treatment for 5 times, and the film layer was cured by keeping it at 100°C for 3 hours to obtain a low-absorption and high-emission anti-corrosion thermal control coating on the surface of the aluminum alloy. The surface modifier used had an average particle size of 20nm and a concentration of 10wt% for silica sol; the metal thermal control salt was zinc sulfate with a concentration of 1wt%. The solvent of the surface modifier was a mixture of ethanol and pure water in a volume ratio of 1:1.

[0033] The low-absorption and high-emission anti-corrosion thermal control coating on the surface of the aluminum alloy prepared in this embodiment has a thickness of 80 μm, a bonding strength of level 1, a solar absorptivity of 0.22, an infrared emissivity of 0.88, a salt spray resistance of ≥ 850 h, a moisture and heat resistance of ≥ 1200 h, and no damage or falling off occurs after 100 thermal cycles at -196°C to +100°C.

[0034] Embodiment 2:

[0035] This embodiment provides a method for preparing a low-absorption and high-emission anti-corrosion thermal control coating on an aluminum alloy surface, which is specifically prepared according to the following steps:

[0036] (1) using 200 mesh white corundum to sandblast the aluminum alloy (7055), then using acetone and alcohol to clean the surface of the aluminum alloy after sandblasting, and using compressed air to dry it to obtain the alloy after pretreatment;

[0037] (2) placing the aluminum alloy treated in step (1) in an electrolytic cell, with the aluminum alloy as the anode and the stainless steel electrolytic cell as the cathode, and using a pulsed micro-arc oxidation power supply to supply power at a current density of 8A·dm -2 , forward voltage 600V, power frequency 500Hz, duty cycle 50%, electrolyte temperature 35℃, pH value 9, reaction for 30min, to obtain a low absorption, medium and high emissivity thermal control coating (initial thermal control coating) grown in situ on the surface of aluminum alloy. The electrolyte used includes Na2SiO3, Na3PO4 and K2ZrF6, the concentration of Na2SiO3 is 15g / L; the concentration of Na3PO4 is 15g / L, and the concentration of K2ZrF6 is 1.5g / L.

[0038] (3) An anti-corrosion / thermal control enhanced surface modifier was prepared using silica sol and metal thermal control salt as raw materials. The surface modifier was sprayed on the surface of the aluminum alloy after micro-arc oxidation treatment for 5 times, and the film layer was cured by keeping it at 80°C for 5 hours to obtain a low-absorption and high-emission anti-corrosion thermal control coating on the surface of the aluminum alloy. The surface modifier used had an average particle size of 50nm and a concentration of 15wt% for silica sol; the metal thermal control salt was silver nitrate with a concentration of 2wt%. The solvent of the surface modifier was a mixture of ethanol and pure water in a volume ratio of 1:1.

[0039] The low-absorption and high-emission anti-corrosion thermal control coating on the surface of the aluminum alloy prepared in this embodiment has a thickness of 95 μm, a bonding strength of level 1, a solar absorptivity of 0.20, an infrared emissivity of 0.89, a salt spray resistance of ≥ 870 h, a moisture and heat resistance of ≥ 1000 h, and no damage or falling off occurs after 100 thermal cycles at -196°C to +100°C.

[0040] Embodiment 3:

[0041] This embodiment provides a method for preparing a low-absorption and high-emission anti-corrosion thermal control coating on an aluminum alloy surface, which is specifically prepared according to the following steps:

[0042] (1) using 200 mesh white corundum to sandblast an aluminum alloy (2A12), then using acetone and alcohol to clean the alloy surface after sandblasting, and using compressed air to dry it to obtain a pre-treated alloy;

[0043] (2) placing the aluminum alloy treated in step (1) in an electrolytic cell, with the aluminum alloy as the anode and the stainless steel electrolytic cell as the cathode, and using a pulsed micro-arc oxidation power supply to supply power at a current density of 10 A·dm -2 , forward voltage 450V, power frequency 500Hz, duty cycle 50%, electrolyte temperature 25℃, pH value 9, reaction for 40min, to obtain a low absorption, medium and high emissivity thermal control coating (initial thermal control coating) grown in situ on the surface of aluminum alloy. The electrolyte used includes Na2SiO3, Na3PO4 and K2ZrF6, the concentration of Na2SiO3 is 12g / L; the concentration of Na3PO4 is 12g / L, and the concentration of K2ZrF6 is 1.5g / L.

[0044] (3) An anti-corrosion / thermal control enhanced surface modifier was prepared using silica sol and metal thermal control salt as raw materials. The surface modifier was sprayed on the surface of the aluminum alloy after micro-arc oxidation treatment for 5 times, and the film layer was cured by keeping at 90°C for 3 hours to obtain a low-absorption and high-emission anti-corrosion thermal control coating on the surface of the aluminum alloy. The surface modifier used had an average particle size of 70nm and a concentration of 15wt% for silica sol; the metal thermal control salt was magnesium phosphate with a concentration of 2wt%. The solvent of the surface modifier was a mixture of ethanol and pure water in a volume ratio of 1:1.

[0045] The low-absorption and high-emission anti-corrosion thermal control coating on the surface of the aluminum alloy prepared in this embodiment has a thickness of 110 μm, a bonding strength of level 1, a solar absorptivity of 0.23, an infrared emissivity of 0.92, a salt spray resistance of ≥ 850 h, a moisture and heat resistance of ≥ 1300 h, and no damage or falling off occurs after 100 thermal cycles at -196°C to +100°C.

[0046] Comparative Example 1

[0047] Using 7A04 aluminum alloy as the substrate, a comparative coating was prepared according to the following steps:

[0048] (1) using 200 mesh white corundum to sandblast an aluminum alloy (7A04), then using acetone and alcohol to clean the surface of the aluminum alloy after sandblasting, and using compressed air to dry it to obtain a pre-treated aluminum alloy;

[0049] (2) placing the aluminum alloy treated in step (1) in an electrolytic cell, with the aluminum alloy as the anode and the stainless steel electrolytic cell as the cathode, and using a pulsed micro-arc oxidation power supply to supply power at a current density of 6 A·dm -2 The coating on the surface of the aluminum alloy was obtained by reacting for 30 minutes under the conditions of forward voltage of 550V, power frequency of 500Hz, duty cycle of 50%, electrolyte temperature of 60℃ and pH value of 9. The electrolyte used includes Na2SiO3, and the concentration of Na2SiO3 is 10g / L.

[0050] (3) A surface modifier was prepared using silica sol as a raw material, and the surface modifier was sprayed on the surface of the aluminum alloy after micro-arc oxidation treatment for 5 times, and the film layer was cured by heat preservation at 100°C for 3 hours to obtain an aluminum alloy surface coating. The surface modifier used had an average particle size of 40 nm and a concentration of 10 wt%. The solvent of the surface modifier was a mixture of ethanol and pure water in a volume ratio of 1:1.

[0051] The low-absorption and high-emission anti-corrosion thermal control coating on the surface of the aluminum alloy prepared in this embodiment has a thickness of 75 μm, a bonding strength of level 1, a solar absorptivity of 0.34, an infrared emissivity of 0.77, a salt spray resistance of ≥ 850 h, a moisture and heat resistance of ≥ 1200 h, and no damage or falling off occurs after 100 thermal cycles at -196°C to +100°C.

[0052] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0053] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms should not be understood as necessarily referring to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification.

[0054] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

[0055] The above is a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for preparing a low-absorption and high-emission anti-corrosion thermal control coating on an aluminum alloy surface, characterized in that: include: S1, placing the pre-treated aluminum alloy as an anode in an electrolytic cell, using a pulsed micro-arc oxidation power supply to electrolyze the electrolyte in the electrolytic cell to obtain an initial thermal control coating formed on the surface of the pre-treated aluminum alloy, wherein the electrolyte comprises phosphate, silicate and zirconate, the concentration of phosphate is 1 to 20 g / L, the concentration of silicate is 1 to 20 g / L, and the concentration of zirconate is 0.1 to 5 g / L; S2, coating the surface modifier on the surface of the aluminum alloy treated in step S1, and forming a low-absorption and high-emission anti-corrosion thermal control coating on the surface of the aluminum alloy after the surface modifier is solidified, wherein the surface modifier includes silica sol and metal thermal control salt, the metal thermal control salt includes at least one of zinc sulfate, silver nitrate, and magnesium phosphate, the particle size range of the silica sol is 10 to 80 nm, the concentration of the silica sol is 5 to 20 wt%, and the concentration of the metal thermal control salt is 0.1 to 5 wt%.

2. The method for preparing the low-absorption and high-emission anti-corrosion thermal control coating on the surface of aluminum alloy according to claim 1, characterized in that: In step S1, the electrolyte in the electrolytic cell is electrolyzed at a current density of 1A·dm -2 ~30A·dm -2 , forward voltage 300V~650V, power supply frequency 50Hz~2000Hz, duty cycle 10%~60%.

3. The method for preparing the low-absorption and high-emission anti-corrosion thermal control coating on the surface of aluminum alloy according to claim 1, characterized in that: In step S1, the temperature of the electrolyte is 10-40° C. and the pH value is 8.5-14.0; the time for electrolyzing the electrolyte in the electrolytic cell is 5-60 minutes.

4. The method for preparing the low-absorption and high-emission anti-corrosion thermal control coating on the surface of aluminum alloy according to claim 1, characterized in that: Step S2 includes: The surface modifier is coated on the surface of the aluminum alloy treated in step S1 by spraying, and the surface modifier is cured by keeping at 60-100° C. for 2-8 hours to obtain a low-absorption and high-emission anti-corrosion thermal control coating on the surface of the aluminum alloy, wherein the number of spraying is 3-8 times.

5. The method for preparing the low-absorption and high-emission anti-corrosion thermal control coating on the surface of aluminum alloy according to claim 1, characterized in that: The phosphates include Na3PO4, Na5P3O 10 At least one of .

6. The method for preparing the low-absorption and high-emission anti-corrosion thermal control coating on the surface of aluminum alloy according to claim 1, characterized in that: The silicate includes at least one of Na2SiO3 and K2SiO3.

7. The method for preparing a low-absorption and high-emission anti-corrosion thermal control coating on an aluminum alloy surface according to claim 1, characterized in that: The zirconate includes at least one of K2ZrF6 and Zr(NO3)4.

8. The method for preparing a low-absorption and high-emission anti-corrosion thermal control coating on an aluminum alloy surface according to claim 1, characterized in that: Before step S1, the method further includes: The aluminum alloy is sandblasted with 150-250 mesh white corundum, and the surface of the aluminum alloy after sandblasting is cleaned with acetone and alcohol in sequence, and dried with compressed gas to obtain the aluminum alloy after pre-treatment.

9. A low-absorption and high-emission anti-corrosion thermal control coating on the surface of aluminum alloy, characterized in that: It is prepared by the method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Method for sealing aluminum alloy anodic oxide film pores through using silica sol

    CN102732934A

  • Preparation method of composite ceramic coating layer

    CN104911662A